MOTIVATION: STRATEGY OR SELF FULFILLMENT FOR POSITIVE SCHOOLING - Galván Oré, Liliana (2008)
As of the 1960’s, the concept of motivation has been worked by humanist psychologists as a necessary impulse to cover achievement needs, affiliation or power, as defined by McClelland, or self fulfillment needs, according to Maslow. These ideas lead people to evaluate their purpose in life and in what way their search for self fulfillment or auto realization and the well-being of others, is really a part of their own script and personal vision.On the other hand, motivation pedagogy surges as a response to a need of involving the students during the teaching-learning process. In this case, motivation is understood as a phase during the process, in which the professor assumes the responsibility of creating strategies to emotionally involve the students with the development of the subject.However, what is the purpose of using motivation strategies so that the students involve themselves in the learning process, if the teacher doesn’t feel motivated with the task? Will the students be able to separate the learning process of contents and new skills from learning behaviors that an unmotivated professor could be transmitting? Is it possible to challenge without having your own personal goals? Can one present a stimulus for the rest of the people to use it and be motivated by it without trying it first?And on the other hand, to what degree can you demand the teacher to have a clear motivation for learning, if the school does not orient itself towards achievements, towards recognition or feedback. If the school only commits with results but not with the procedures, can it be possible that the teacher, within this context, will dare to invent and build, in an independent manner, new tools and be able to sustain his or her motivation even though it is not recognized?These are the questions that serve as a base for the exposition of the subject with the purpose of exploring in what way professors can be motivating agents of their own lives as well as of the teaching-learning process.